Modelling ischemia-reperfusion injury (IRI) in vitro using metabolically matured induced pluripotent stem cell-derived cardiomyocytes - Alejandro Hidalgo; Nick Glass; Dmitry Ovchinnikov; Seung-Kwon Yang; Xinli Zhang; Stuart Mazzone; Chen Chen; Ernst Wolvetang; Justin Cooper-White (APL Bioengineering, 2018)
Coronary intervention following ST-segment elevation myocardial infarction (STEMI) is the treatment of choice for reducing cardiomyocyte death but paradoxically leads to reperfusion injury. Pharmacological post-conditioning is an attractive approach to minimize Ischemia-Reperfusion Injury (IRI), but candidate drugs identified in IRI animal models have performed poorly in human clinical trials, highlighting the need for a human cell-based model of IRI. In this work, we show that when we imposed sequential hypoxia and reoxygenation episodes [mimicking the ischemia (I) and reperfusion (R) events] to immature human pluripotent stem cell-derived cardiomyocytes (hPSC-CMs), they display significant hypoxia resistance and minimal cell death (∼5%). Metabolic maturation of hPSC-CMs for 8 days substantially increased their sensitivity to changes in oxygen concentration and led to up to ∼30% cell death post-hypoxia and reoxygenation. To mimic the known transient changes in the interstitial tissue microenvironment during an IRI event in vivo, we tested a new in vitro IRI model protocol that required glucose availability and lowering of media pH during the ischemic episode, resulting in a significant increase in cell death in vitro (∼60%). Finally, we confirm that in this new physiologically matched IRI in vitro model, pharmacological post-conditioning reduces reperfusion-induced hPSC-CM cell death by 50%. Our results indicate that in recapitulating key aspects of an in vivo IRI event, our in vitro model can serve as a useful method for the study of IRI and the validation and screening of human specific pharmacological post-conditioning drug candidates.